2001
DOI: 10.1089/109264201317054564
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy for Symptomatic Gallstones in Diabetic Patients

Abstract: Although they had the same symptoms and laboratory findings, laparoscopic cholecystectomy in diabetic patients is associated with more morbidity and a higher conversion rate than in nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 13 publications
1
21
1
2
Order By: Relevance
“…We ensure that the coagulopathy, if present, is corrected before surgery. Unlike the study of Bedirli,16 which found that LC is associated with more morbidity and a higher conversion rate in patients with diabetes than in those with no diabetes, we found that while carrying out LC, the conversion rate was not significantly different between patients with diabetes mellitus and those without. High total white blood cell count and C-reactive protein level, signs of inflammation in univariate analysis but not in multivariate, predicate much higher conversion rates.…”
Section: Discussioncontrasting
confidence: 99%
“…We ensure that the coagulopathy, if present, is corrected before surgery. Unlike the study of Bedirli,16 which found that LC is associated with more morbidity and a higher conversion rate in patients with diabetes than in those with no diabetes, we found that while carrying out LC, the conversion rate was not significantly different between patients with diabetes mellitus and those without. High total white blood cell count and C-reactive protein level, signs of inflammation in univariate analysis but not in multivariate, predicate much higher conversion rates.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies had found diabetes as a predictor of difficult laparoscopic cholecystectomy. 5,11 Kanaan SA, Murayama KM, in 2002 found that patients with a history of cardiovascular disease (hypertension) had an increased risk for conversion to open cholecystectomy in both the acute and chronic cholecystitis groups particularly in male sex.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) has been consistently shown to be associated with CTO [18,25,42]. Diabetics undergoing LC have a 2.5 times higher risk for CTO than nondiabetic patients (OR = 2.5; 95% CI: 1.3-4.4, P = 0.003) [43].…”
Section: Actual Problems Of Emergency Abdominal Surgerymentioning
confidence: 99%